Can sports participation be a protective factor against suicide-related outcomes in adolescents: a systematic review - Huo, Meilin; Yang, Zhen; Yang, Li; Chen, Sitong (Frontiers in Psychology, 2024)
Background: Suicide-related outcomes of adolescents have become a serious public health problem worldwide. Emerging evidence suggests that sports participation may interact with suicide-related outcomes. The objective of this systematic review is to investigate the association between sports participation and suicide-related outcomes among adolescents. Design: A systematic review according to PRISMA Statement (International Platform of Registered Systematic Review and Meta-Analysis Protocols registration: INPLASY202330072). Methods: The literature search was conducted in three electronic databases: Web of Science, PubMed, and EBSCOhost. Results: A total of sixteen studies (twelve cross-sectional studies, three prospective cohort studies, and one longitudinal study) met the inclusion criteria were evaluated. Strong consistent evidence was found for the negative association between suicidal ideation, suicide attempts, and sports participation among adolescents. There was insufficient evidence to support consistency in the association between sports participation and suicide plans, and no evidence of gender differences between sports participation and these three suicide-related outcomes. Furthermore, there was heterogeneity in the measures of sports participation and suicide-related outcomes in the included studies. Conclusion: Evidence suggests that more sports participations are associated with lower suicidal ideation and suicide attempts in adolescents. However, the directionality of the observed associations should be examined with increasing high-quality longitudinal studies in the future.